EFEKTIVITAS KONSELING KELOMPOK REALITA UNTUK MENURUNKAN TINGKAT PROKASTINASI AKADEMIK MAHASISWA BK ANGKATAN 2021 - Sherly Rahmadani Izza; Yurike Kinanthy Karamoy; Fakhruddin Mutakib (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Maladaptive behavior in education is still common. Academic procactination is one of the maladaptive behaviors that is often found among students and university students. Academic procrastination is the behavior of procrastinating in doing academic tasks. This behavior is a behavior that must be overcome so that the procrastinator can achieve his developmental task optimally. As many as 80% of BK students class of 2021 Universitas Islam Jember are still experiencing academic procastination. This study aims to determine the effectiveness of reality group counseling in reducing the academic procastination rate of BK students class of 2021. This research is a type of quantitative research with an experimental method using a one group pre-test pos-test design. The sample used in the study was 5 BK students class of 2021 with the criteria of having a high level of academic procastination based on the results of filling out the questionnaire. The collection method used is using a Likert scale and then the data is analyzed using the SPSS application version 28.00 with the paired Samples Test formula. The results showed that reality group counseling was effective in reducing the level of academic procastination of students.